2022
DOI: 10.1108/jpbm-02-2022-3851
|View full text |Cite
|
Sign up to set email alerts
|

Social media influencers’ community and content strategy and follower engagement behavior in the presence of competition: an Instagram-based investigation

Abstract: Purpose Drawing on insights from social influence theory, the MAIN model of digital media affordances and the literature on the attention economy, this study aims to investigate how social media influencers’ community and content strategy contribute to follower engagement behavior in the presence of competition. Design/methodology/approach This study used a web-scraped data set of Instagram influencers. It measured community strategy using influencers’ number of followers, number of following and breadth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…Although the three-way interaction effects among the independent variables were the main interest in this study, the results revealed that the main and interaction effects of domain breadth and follower number were all significant. Consistent with prior literature (Tafesse and Wood, 2022;Gross and Wangenheim, 2018), the findings supported that follower counts and breadth of expertise domain, which are cues readily available by reviewing an influencer's profile page and previous posts, significantly predicted consumer attitudinal and behavioral responses to influencer endorsements. Thus, brand managers should review the recent posts of influencers, and their follower counts when deciding which influencers to partner with.…”
Section: Practical Implicationssupporting
confidence: 87%
See 1 more Smart Citation
“…Although the three-way interaction effects among the independent variables were the main interest in this study, the results revealed that the main and interaction effects of domain breadth and follower number were all significant. Consistent with prior literature (Tafesse and Wood, 2022;Gross and Wangenheim, 2018), the findings supported that follower counts and breadth of expertise domain, which are cues readily available by reviewing an influencer's profile page and previous posts, significantly predicted consumer attitudinal and behavioral responses to influencer endorsements. Thus, brand managers should review the recent posts of influencers, and their follower counts when deciding which influencers to partner with.…”
Section: Practical Implicationssupporting
confidence: 87%
“…Wiedmann and von Mettenheim (2021) empirically examined the impact of influencer expertise on consumers’ brand satisfaction by manipulating the influencer’s education such that an influencer who endorsed a fashion brand had studied fashion design (high expertise) or computer science (low expertise). Tafesse and Wood (2022) also investigated the impact of influencers’ breadth of interest on follower engagement by examining how the number of domains of interest listed on influencers’ profile pages affected the number of likes and comments that they received. In addition to the direct cues on profile pages, influencers can brand themselves as experts in a particular domain of interest based on what they post (De Cicco et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this way, they are more compelling to be imitated as role models. In addition to using indicators such as the number of followers (Tafesse and Wood, 2023) and the quality and quantity of posts (Barta et al , 2023) to decide which SMI to work with, such criteria could help brand managers set up a good starting point and develop potentially more effective influencer marketing strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Following this perspective, consumer engagement is defined as “as the customers’ behavioural manifestation towards a brand or firm, beyond purchase, resulting from motivational drivers” (van Doorn et al , 2010, p. 254). These behavioral manifestations prompted by motivational drivers can inform marketers about the kinds of content that fuel such behaviors particularly on social media (Tafesse and Wood, 2022).…”
Section: Introductionmentioning
confidence: 99%